Could industrialization and renewable energy enhance environmental sustainability: An empirical analysis for Sub-Saharan Africa? - Ndzembanteh Aboubakary Nulambeh; Haruna Babatunde Jaiyeoba (World Development Sustainability)
Industrialization has led to numerous environmental issues, prompting both industrialized and developing countries to adopt sustainable practices. This research investigates the impact of renewable energy and industrialization on the ecological footprint in Africa using the GMM method with data that span from 2006 to 2020 due to data availability. The findings reveal that renewable energy significantly reduces the level of ecological footprint, while industrialization raises it and thus detrimental to the environment. However, industrialization can enhance environmental sustainability if driven by renewable energy use since renewable energy has the potentials in contributing to sustainable development. It equally helps in mitigating climate change by reducing greenhouse gas emissions and contributing to a cleaner environment. These results therefore underscore the importance of sustainable development and environmental protection in Sub Saharan Africa. The study thus recommends that African countries improve their industrial and institutional frameworks through policies that promote renewable energy investments, support domestic low-carbon technology for producers and phase out fossil fuel subsidies. Additionally, policymakers should implement carbon pricing to incentivize companies to adopt more sustainable practices.